Relationship of Cholinesterase Activity with Blood Glucose Levels Due to Pesticide Exposure to Farmers in Mlokorejo Village - Muhammad Ryznar Faisal Nur Luqmani; Kristianningrum Dian Sofiana; Bagus Hermansyah (Faculty of Medicine, University of Jember, 2021)
Increase in blood glucose levels can be caused by the long-term use of pesticides by farmers. This study aims to determine whether there is a correlation between the activity of cholinesterase as an indicator of exposure to pesticides and blood glucose of farmers in Mlokorejo Village, Jember Regency. The research method is observational-analytic with a cross-sectional study design. Data in the form of general characteristics of the sample were obtained through interviews, while the data of the activity of cholinesterase and blood glucose levels of farmers were obtained at the Biochemical Laboratory of the Faculty of Medicine, Jember University. The sample size of this study is 30 samples. All of the samples are having an increased activity of cholinesterase. Most of the samples are having normal blood glucose levels. Based on the results of statistical analysis using the Spearman correlation test (a= 0.05), it was concluded that there was no significant correlation between the two variables (p = 0,191). Keywords: blood glucose, cholinesterase, pesticides